تطوير مواد مهارة الكلام القائمة على الوظائف اللغوية حول الصحة - Zahra, Nabila Himmatina; Royani, Ahmad; Mahyudin, Erta (Department of Arabic Education - Faculty of Educational Sciences, 2023)
The researcher chose this topic because teaching speaking skill didn’t success in promote students’ competence in speaking. One of the problems is the lack of dialogue exercises material, which leads to a lack of opportunity in doing conversation, especially about health. There are no abstract materials and patterns of expressions of health. The research aims to develop speaking materials based on language functions about health. The researcher used R&D method with a qualitative approach. Its use the ADDIE model: analysis, design, development, implementation, and evaluation. The research shows that: (1) the speaking materials based on language functions about health supports in teaching speaking skill contains four materials: vocabulary, listening, speaking, and grammar. (2) The developed materials show their quality after being assessed by the expert in